2016
DOI: 10.1111/jcpe.12640
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical response to treatment and maintenance of localized aggressive periodontitis: a cohort study

Abstract: Aim To evaluate long-term clinical response to periodontal therapy and maintenance in localized aggressive periodontitis (LAP). Materials and Methods One hundred forty-one African-Americans diagnosed with LAP, aged 5–25 years, were enrolled. Patients underwent periodontal mechanical debridement plus one week of amoxicillin/metronidazole. Mechanical therapy was repeated as needed and clinical parameters were recorded at baseline, 3, 6, 12, 18, and 24 months, and 2 additional annual follow-up visits after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 52 publications
1
41
0
1
Order By: Relevance
“…These correlations presented here provide further evidence for implication of the JP2 genotype as an associated pathogen in LAgP disease, attesting for the first time the effectiveness of this non‐surgical treatment protocol for this population at 12 months after therapy. In fact, long‐term clinical benefits and 4‐year maintenance of this treatment protocol has been previously reported for all patients with LAgP in another trial 36 . It is noteworthy that this is a one‐time regimen of antibiotics for treatment of this population at baseline, and the patients are followed by regular maintenance after this treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These correlations presented here provide further evidence for implication of the JP2 genotype as an associated pathogen in LAgP disease, attesting for the first time the effectiveness of this non‐surgical treatment protocol for this population at 12 months after therapy. In fact, long‐term clinical benefits and 4‐year maintenance of this treatment protocol has been previously reported for all patients with LAgP in another trial 36 . It is noteworthy that this is a one‐time regimen of antibiotics for treatment of this population at baseline, and the patients are followed by regular maintenance after this treatment.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, longterm clinical benefits and 4-year maintenance of this treatment protocol has been previously reported for all patients with LAgP in another trial. 36 It is noteworthy that this is a one-time regimen of antibiotics for treatment of this population at baseline, and the patients are followed by regular maintenance after this treatment. Thus, significant reduction of this pathogen in the long term with one-time antibiotic use is of extreme clinical benefit for this disease.…”
Section: Jp2 Reduction In Localized Aggressive Periodontitismentioning
confidence: 99%
“…A retrospective analysis of permanent dentition cases of our studied population showed that out of 23 cases of LAP in permanent dentition that previous radiographs could be obtained from their primary dentition ages, onset of bone loss at primary dentition was observed in 20 of them (87%), affecting them as early as 5 years of age. 14 Thus, treatment of this disease at early stages could prevent the progression of disease into permanent teeth, as suggested previously. 13,15,16 …”
Section: Introductionmentioning
confidence: 70%
“…In fact, several authors documented clinical improvement in PD, PAL, and BOP. [1718] Mongardini et al . compared the effectiveness between FMDP and conventional treatment in 16 patients with AgP (referred as early-onset periodontitis) and ascertained small but significant differences in periodontal indexes over an 8-month period.…”
Section: Discussionmentioning
confidence: 99%